If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -1k = 7k + -5k Combine like terms: 7k + -5k = 2k 6 + -1k = 2k Solving 6 + -1k = 2k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-2k' to each side of the equation. 6 + -1k + -2k = 2k + -2k Combine like terms: -1k + -2k = -3k 6 + -3k = 2k + -2k Combine like terms: 2k + -2k = 0 6 + -3k = 0 Add '-6' to each side of the equation. 6 + -6 + -3k = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -3k = 0 + -6 -3k = 0 + -6 Combine like terms: 0 + -6 = -6 -3k = -6 Divide each side by '-3'. k = 2 Simplifying k = 2
| 25x-8=72 | | (180-x)=4x | | 4a=(180-x) | | e^2z+1=0 | | 6x*6xy= | | x^3-25x^2=15 | | 2f(3f+2)=3 | | -8x+8(1+4x)=152 | | 6xy+6x= | | 2c-6=2c+1 | | x^3-25*x^2=15 | | 3(x+3)=3(x+14) | | 0.03x^2-1.2x+17=0 | | r+4=-7 | | 10(x+4)=10(x+11) | | 3-5=4t+2t | | 6z^2=7 | | 8(x+3)=8(x+14) | | 3t+3x+1=0 | | -1n+2+3n=-6 | | 8x^2+0.9x=0.06 | | 10x-3=18x+17 | | 10x-3=18x+7 | | -4b-3=2b-5 | | 6/x-52=15/x-2 | | 3=3-4n-3n | | y=0.5x^2+4x | | 36x^2+13x-40=0 | | 8-8a=2 | | Y+13=-1[x+3] | | 2-6/3=-5/2 | | -20=-2n-3n-5 |